Influence of Exposure to Benzo[a]pyrene on Mice Testicular Germ Cells during Spermatogenesis - Hueiwang Anna Jeng; Silvina M. Bocca (Journal of Toxicology)
The objective of this study was to assess the toxicological effect of exposure to benzo(a)pyrene, B[a]P, on germ cells during spermatogenesis. Mice were exposed to B[a]P at 1, 10, 50, and 100 mg/kg/day for 30 days via oral ingestion. Germ cells, including spermatogonia, spermatocytes, pachytene spermatocytes, and round spermatids, were recovered from testes of mice exposed to B[a]P, while mature spermatozoa were isolated from vas deferens. Reproductive organs were collected and weighed. Apoptotic response of germ cells and mature spermatozoa were qualified using the terminal deoxynucleotidyl transferase mediated deoxy-UTP nick end labeling (TUNEL) assay. B[a]P exposure at ≤10 mg/kg/day for 30 days did not significantly alter concentrations of germ cells and mature spermatozoa and apoptotic response in germ cells and mature spermatozoa. Exposure to B[a]P at 50 and 100 mg/kg/day induced testicular atrophy and yielded a significant reduction in the concentrations of spermatogonia, spermatocytes, pachytene spermatocytes, and round spermatid cells as compared with the control. Also, mature spermatozoa experienced decreased concentrations and viability. B[a]P-exposed mice experienced a significant increase in apoptotic germ cells as compared to the control mice. However, the mice dose concentrations were not relevant for comparison to human exposure.